Reconstruction of the post-glacial volcanic activity in Iceland through paleomagnetic survey and remote sensing - Pinton, Annamaria (Università degli studi Roma Tre, 2015)
Iceland covers an area of about 103’000 km2, the 22% of which (~23’000 km2) is covered by Holocene volcanic deposits, mainly basaltic or basaltic-andesitic in composition. The number of volcanoes and eruptive fissures present in Iceland is so huge, that they have been subdivided and organized in 30 volcanic systems, mainly active during Holocene epoch. Sixteen of these volcanic systems were active after the settlement of Iceland (dated 871 AD) in historical times, erupting nearly 40 km3 of lavas. The other twelve systems erupted about 200 km3 of lavas prior to 871 AD, mainly from shield volcanoes and eruptive fissures. All these eruptions, although effusive, had a very strong in impact on climate because of the dangerous SO2 emissions into the atmosphere: the famous Laki eruption in 1783-84 AD caused severe famine and haze all over Europe, as other big effusive eruptions did, both in Iceland and all over the world. Therefore, the assessment of their frequency in time is, of course, very important. In general, a detailed chronostratigraphy of the eruptive events exists only for historical eruptions. On the other hand, the majority of the pre-historical events has been only partially studied: ages and volumes estimates mostly come from unpublished works and personal communications to authors and it is not possible to retrieve a detailed geological map for the majority of the biggest events. The difficulty in studying those volcanic events lies in different aspects: - a high uncertainty on identifying lavas distributions because of the high compositional similarity between basaltic lavas and, yet, their high internal petrographic variability within same event; this results in a difficult correlation of distant deposits and on the subsequent difficulty in retrieving precise volume calculations; - difficult application of the radiometric absolute dating methods because of the low K content and the lack of suitable phenocrysts in these recent basaltic lavas, which makes it impossible to apply the 39Ar/40Ar dating. Seemingly, the 14C dating method relies on the presence of paleosoils and vegetation remains, which are quite rare at these latitudes. This means that only scattered spots of hardly correlable lavas have an absolute age constrain, in areas where the relative chronostratigraphy of events is already so tricky; - the tephrochronology (through which dated Holocene felsic tephras, preserved between undated basaltic lavas, can provide an age constrain and a relative date to the basaltic events) it is not always of help because and, at most localities, silicic tephra are not preserved between basaltic lavas (particularly in the inner areas where the weathering caused, for example, by intense precipitations, snow melting or wind is severe). As a conclusion, the complete reconstruction of the chronostratigraphy of huge basaltic events is not always possible and still considerably incomplete. This PhD research project aimed at applying other techniques for solving these problems of absolute datings of Holocene basaltic lavas and their areal correlation. In particular, I used the paleomagnetic method as a correlation and dating tool for deepening the knowledge of the most important Holocene basaltic lavas in Iceland, in terms of age and distribution. This, by collecting samples from multiple lava outcrops and, then, by studying and comparing their registered paleomagnetic direction. Also, a technique that integrates proximal and remote sensing has been developed on a testing area: rock samples and in-situ reflectances were collected and analysed, integrating the acquired information with Landsat 8 satellite images. The application of this method to wider areas opens-up a possible future application of the method to retrieve a correlation between distant deposits by analysing their spectral signatures. The developed research project proved that these methodologies (paleomagnetism and remote/proximal sensing) can be successfully applied and integrated with the available knowledge on the studied volcanic systems for further deepen the understanding of the chronostratigraphy of Icelandic post-glacial (Holocene) volcanic areas. Indeed, they could result in a great help for better constraining the absolute age of deposits, as well as their distribution.